Bibliometrics for Halal Transportation and Occupational Health and Safety - Risdianto Risdianto; Wiwi Hartati; Indah Nursuprianah; Nuraida Absharina Awanis (Journal of General Education and Humanities, 2025)
This study analyzes literature on halal transportation and occupational health and safety (OHS) using a bibliometric approach. A bibliometric analysis was chosen because it systematically maps research trends, identifies key contributors, and highlights thematic linkages, providing a comprehensive overview of the field. Halal transportation integrates Islamic principles into transportation operations, while OHS ensures the health and safety of workers and users. The study retrieves data from Google Scholar, Dimensions, and ScienceDirect using Publish or Perish and VOSviewer to evaluate trends, geographical distribution, and topic linkages. The results indicate that halal transportation research primarily focuses on halal logistics, whereas studies on the operational aspects of non-food goods transportation remain limited. Research on OHS within halal transportation is also scarce, particularly in integrating halal standards with OHS regulations. Malaysia and Indonesia have been the main contributors to this field, with an increasing publication trend since 2010. The main research clusters include "halal logistics," "occupational health and safety," and "sustainability.". This study emphasizes the importance of developing operational standards for halal transportation that incorporate process halalness, worker health and safety, and resource efficiency. It recommends using modern technology, such as IoT, to enhance halal tracking and risk mitigation. By bridging the gap between halal transportation and OHS, this research provides valuable insights for policymakers, industry practitioners, and academics to develop more comprehensive and effective standards. The findings serve as a foundation for future studies on the intersection of transportation operations and OHS.